2002
DOI: 10.1001/archinte.162.14.1625
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Malaria in Travelers to Areas Where Malaria Is Endemic

Abstract: Malaria should be suspected in all patients presenting with complaints after travel to an area where malaria is endemic, and these patients should undergo blood microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 25 publications
1
37
0
2
Order By: Relevance
“…In our patients, 185 (95.4%) malaria patients had thrombocytopenia, with severe cases (Ͻ50,000 platelets/l) accounting for 21.6% of patients. The presence of thrombocytopenia is more common in malaria than in other febrile disease, but it has only a limited role in the prediction of malaria due to its low sensitivity and specificity (1). Our findings show that the presence of thrombocytopenia can have a role in the rapid diagnosis of vivax malaria in that all patients with a positive SD Bioline Malaria Antigen test when thrombocytopenia was present had a positive microscopic examination.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our patients, 185 (95.4%) malaria patients had thrombocytopenia, with severe cases (Ͻ50,000 platelets/l) accounting for 21.6% of patients. The presence of thrombocytopenia is more common in malaria than in other febrile disease, but it has only a limited role in the prediction of malaria due to its low sensitivity and specificity (1). Our findings show that the presence of thrombocytopenia can have a role in the rapid diagnosis of vivax malaria in that all patients with a positive SD Bioline Malaria Antigen test when thrombocytopenia was present had a positive microscopic examination.…”
Section: Discussionmentioning
confidence: 70%
“…Although the symptoms of malaria are very nonspecific and overlap those of other febrile illness, thrombocytopenia has been reported to be associated with vivax malaria as well as with falciparum malaria (14,20,22) and is more common with malaria than with other febrile diseases (7,15,17). Recent studies have also demonstrated the high predictive value of thrombocytopenia in the diagnosis of malaria (1)(2)(3). However, as a substantial proportion of cases falciparum malaria was included in those studies, the predictive value of thrombocytopenia in the diagnosis of vivax malaria would have been limited.…”
mentioning
confidence: 99%
“…For example, several studies indicate that men tend to have higher parasitemia than women (23,32,52). In a recent prospective study of imported malaria cases in France, men reported more severe symptoms of malaria infection (e.g., chills, fever, and low platelet counts) than did women (7). Among Ghanaian school children, although the prevalence of P. falciparum infection does not differ between the sexes, the parasite density is significantly higher for boys than girls around puberty (i.e., from ages 8 to 16), suggesting that circulating sex steroids may influence this outcome (23).…”
Section: Vol 74 2006 Sex Difference In Malaria Infection 3197mentioning
confidence: 97%
“…23 Even when pretravel advice is sought, adherence to travel recommendations, suboptimal in standard travelers, [24][25][26][27] may be worse among VFRs. 28,29 Of 307 Canadians of Asian origin traveling to India, only 31% intended to use malaria chemoprophylaxis and fewer than 10% intended to use mosquito prevention. The majority sought pretravel advice from family practitioners of whom 76% prescribed inappropriate malaria chemoprophylaxis.…”
Section: Barriers To Pretravel Health Advicementioning
confidence: 99%